Law and anthropology - Fikentscher, Wolfgang (C.H. Beck, 2016)
Anthropology of law as a science -- - History, schools, and names of anthropology of law -- Concepts of cultural anthropology -- Social norms (fora) : the theory of law, morals, custom, etiquette, habits, religious norms, political force, conscience -- Theories of culture and cultures -- - Analyses in cultural anthropology -- Biological anthropology in its relation to the anthropology of law -- Kinship patterns, and other anthropological aspects of family and gender law -- Societal order, personhood, and human rights : the anthropology of constitutional justice -- Reciprocity, exchange, gifts, contracting, trust : the anthropology of commutative justice -- Possession, ownership, probate; market and non-market economies, antitrust, cultural property and heritage of mankind : the anthropology of distributive justice -- Torts, crimes, sanctions. Witchcraft and related issues : the anthropology of compensatory or retributive justice -- Jurisdiction. Procedure and dispute settlement. Conflicts of law : the anthropology of jurisdictional justice, of procedural justice, and of conflicts justice -- Native American law -- Ethnic groups. The international law of indigenous peoples. Global human rights -- Applied anthropology of law